THE IMPACT OF MOBILE-ASSISTED LANGUAGE LEARNING ON VOCABULARY RETENTION AMONG ESL STUDENTS - Ibrohimova Nozima (TADQIQOTLAR, 2025)
Abstract: This article explores the effects of mobile-assisted language learning (MALL) on vocabulary retention among learners of English as a Second Language (ESL). As mobile technology becomes increasingly embedded in daily life, its role in language  learning  environments  is  growing.  The  paper  examines  how  mobile applications  and  tools  influence  vocabulary  acquisition  and  long-term  retention, highlighting both the benefits and challenges of their integration into ESL education. Practical recommendations for educators and suggestions for future research are also discussed.